The neural stem cell properties of Pkd2l1+ cerebrospinal fluid-contacting neurons in vivo - Cao, Liang; Huang, Ming-Zhi; Zhang, Qiang; Luo, Zhang-Rong; Zhang, Yi; An, Ping-Jiang; Yang, Lei-Luo; Tan, Wei; Wang, Chun-Qing; Dou, Xiao-Wei; Li, Qing (Frontiers in Cellular Neuroscience, 2022)
The neural stem cells (NSCs) in the ventricular-subventricular zone of the adult mammalian spinal cord may be of great benefit for repairing spinal cord injuries. However, the sources of NSCs remain unclear. Previously, we have confirmed that cerebrospinal fluid-contacting neurons (CSF-cNs) have NSC potential in vitro. In this study, we verified the NSC properties of CSF-cNs in vivo. In mouse spinal cords, Pkd2l1+ CSF-cNs localized around the central canal express NSC markers. In vitro, Pkd2l1+ CSF-cNs form a neurosphere and express NSC markers. Activation and proliferation of CSF-cNs can be induced by injection of the neurotrophic factors basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF) into the lateral ventricle. Spinal cord injury (SCI) also induces NSC activation and proliferation of CSF-cNs. Collectively, our results demonstrate that Pkd2l1+ CSF-cNs have NSC properties in vivo and may be involved in SCI recovery.